1996
DOI: 10.1016/s1359-0278(96)00059-4
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of the intramolecular disulfide bridge to the folding stability of REIv, the variable domain of a human immunoglobulin κ light chain

Abstract: A comparison of the magnitude of the stabilizing effect exerted by the disulfide bond and the length of the mainchain loop framed by it suggests lowering of the entropy of the unfolded state as the sole source of the effect. Disulfide bonds are not necessary for proper folding of immunoglobulin variable domains and can be removed, provided the loss of folding stability is at least partly compensated by stabilizing amino acid exchanges.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
42
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 32 publications
4
42
0
Order By: Relevance
“…Reverse primer [25][26][27][28][29][30][31][32][33][34][35][36]. The data are representative of seven independent experiments.…”
Section: Forward Primermentioning
confidence: 99%
“…Reverse primer [25][26][27][28][29][30][31][32][33][34][35][36]. The data are representative of seven independent experiments.…”
Section: Forward Primermentioning
confidence: 99%
“…A characteristic feature of antibodies is that the intradomain disulfide bond, which connects residues far apart in sequence, is completely buried in the core of the protein. These proteins provide an excellent system to study the folding and assembly of all ␤-sheet proteins and to elucidate the hierarchy of intra/interchain disulfide bond formation during the folding process of multimeric and multidomain proteins (11)(12)(13)(14)(15). The ␤-sheet folding is usually much slower than the ␣-helix formation because amino acid residues, which are far apart in the polypeptide chain, must interact correctly in the three-dimensional space to form stabilizing interactions (16).…”
mentioning
confidence: 99%
“…Indeed, it was found that scFv fragments expressed cytoplasmically in COS cells do not form the disulfide bonds (10). The intradomain disulfide contributes about 4 -5 kcal/mol to the stability of antibody domains (11,12). Therefore, antibody fragments expressed in a reducing environment are strongly destabilized, compared with the same molecules containing disulfides, and a smaller fraction of these fragments is likely to fold to the correct native structure.…”
mentioning
confidence: 99%